Of loans and livelihoods: Gendered "social work" in urban India. Issue 2 (10th May 2018) - Radhakrishnan, Smitha
Abstract : Through an ethnographic study of commercial microlending in urban India, this article examines how "everyday" financialization reinscribes class and gender hierarchies in working‐class communities at global finance's outer edges. Relatively privileged women deploy their knowledge of their communities to organize women, sometimes coercively, into precise formations that meet the exacting requirements of corporate microfinance institutions (MFIs). Through "social work, " powerful volunteers can convert intimate financial knowledge of households in their neighborhoods into social and cultural power. Concomitantly, MFIs aiming to funnel global capital into marginal neighborhoods achieve financial sustainability.